Effects of maternal iron deficiency anemia on the iron stores of the new born- an analytical study - Singla, Reecha; Grover, Suparna; Kumar, Ashwani; Kaur, Sukhraj (International Journal of Research in Medical Sciences, 2025)
Background: The aim of the study was to determine the effect of maternal iron deficiency anemia on neonatal iron stores. Methods: This prospective study was conducted in the department of obstetrics and gynecology, Government Medical College, Amritsar from January 2023 to March 2024. A total of 200 antenatal patients at gestation ≥37 weeks were allotted to four groups: group A (included non-anemic cases), group B (included cases with mild to moderate anemia with hemoglobin 7-10.9 gm/dl), group C included cases with severe anemia with hemoglobin <7 gm/dl) and group D (included treated cases of iron deficiency anemia that had been corrected by therapeutic iron replacement) with 50 patients in each group after written informed consent. Cord hemoglobin and ferritin levels were taken at the time of delivery to see the effect of maternal anemia on neonatal iron stores. Results: A positive correlation between maternal ferritin and neonatal ferritin levels (r2=0.332, p=0.014) and positive correlation between maternal hemoglobin levels and neonatal hemoglobin levels (r2=0.32, p=0.033) was seen indicating maternal anemia during pregnancy impacts the neonatal iron stores at birth. Conclusions: Neonatal hemoglobin as well as iron stores have a positive correlation with maternal hemoglobin and iron stores thus appropriate management of maternal anemia can play a major role in reducing anemia in future generations.